Gokarneshwara or Bisaldeo Temple - Temples of India Project Team (Jio Institute, 2024)
The Gokarneshwara or Bisaldeo Temple in a courtyard built on the Banas river. It is located near the Bisalpur dam. The plan of temple consists of a garbhagriha (sanctum sanctorum), an antarala (vestibule or antechamber), a mahamandapa (pillared hall) with lateral transepts and an ardhamandapa. It is a nirandhara prasada i.e., without the pradakshina path or circumambulatory path. The sanctum is pancharatha (consisting of five projections on each side) in plan and the walls of the sanctum are plain.